Penerapan Media Wordwall untuk Meningkatkan Minat Membaca Siswa Kelas II di Madrasah Ibtidaiyah - Safitri, Anggun; Yulia Sari, Sri; Rahmawati, Sophia (IBTIDA’, 2025)
The main issue at the Nurul Yaqin Private Madrasah Ibtidaiyah is the students’ lack of enthusiasm for reading. This is mostly due to the teacher’s failure to diversify the learning materials and the monotonous nature of the learning process, resulting in a diminished interest in reading among the students. This thesis presents classroom action research that focuses on enhancing students’ enthusiasm for reading through the implementation of Wordwall media in thematic learning of Indonesian language material for second-grade students at Nurul Yaqin Private Madrasah Ibtidaiyah, located in Muaro Jambi Regency. Data was acquired via methods such as observation, interviews, questionnaires, subjective tests, and documentation. The data analysis was conducted utilizing qualitative data analysis techniques, which involved data reduction, data presentation, and drawing conclusions. The research findings demonstrate that the utilization of Wordwall media has the potential to enhance pupils’ inclination towards reading. The rise in students’ enthusiasm for reading can be quantified based on the findings of observations of student learning activities. In cycle I, the average was 71%, while in cycle II it increased to 81%. Additionally, the interest in reading, as assessed through a questionnaire, showed an average of 70% in cycle I, falling under the fairly good category. In cycle II, this percentage rose to 80%, indicating a very good level of interest. Moreover, the students’ interest in reading was further supported by their academic performance, as demonstrated by the direct test results. In cycle I, the average score was 73%, which then increased to 88% in cycle II. Therefore, the findings of the study conducted at the Nurul Yaqin Private Madrasah Ibtidaiyah in Muaro Jambi Regency.